Aplikasi Berbasis Web untuk Penyusunan Laporan SHU Bagi Koperasi Simpan Pinjam - Dinda Virgiarini; Renny Sukawati; Monterico Adrian (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2020)
The Savings and Loans Cooperative generally manages savings and loan members as well as the remaining results of cooperative operations. Management of transactions that occur in the company is still conventionally. This causes the length of the administrative recording process, the difficulty of finding data because the data is not neatly arranged, and allows for calculation errors. This application is solutions to overcome these problems. The functionality possessed by this application are the management of incoming member data, management of member deposits consisting of principal savings, mandatory savings, and voluntary savings, member loans, installments on loans with the flate rate method, and calculation of the results of cooperative operations. In addition, this application is also able to present savings reports, loan reports, general journals, ledgers, business results calculation reports, and balance sheets for cooperative accounting records needed. The method used in designing this application is the System Development Life Cycle (SDLC) method with the model used is waterfall. Based on the tests carried out, this application has been implemented, tested, and can be used. Test applications that have been successfully completed include adding member registration, adding savings, adding loan submissions, disabling members, viewing the general ledger, viewing the report of the business results and viewing the balance sheet. Testing that has been done this application still need the development that is possible, IE application capable to see the history of the recording and installment of members, the application is able to perform the calculation of business results in accordance with the posts of the Division and applications capable of charting the savings, loans, and installment on the loan to facilitate the viewing of the increase or decrease of the functionality.